Altered regulation of flowering expands growth ranges and maximizes yields in major crops - Wang, Fan; Li, Shichen; Kong, Fanjiang; Lin, Xiaoya; Lu, Sijia (Frontiers in Plant Science, 2023)
Flowering time influences reproductive success in plants and has a significant impact on yield in grain crops. Flowering time is regulated by a variety of environmental factors, with daylength often playing an important role. Crops can be categorized into different types according to their photoperiod requirements for flowering. For instance, long-day crops include wheat (Triticum aestivum), barley (Hordeum vulgare), and pea (Pisum sativum), while short-day crops include rice (Oryza sativa), soybean (Glycine max), and maize (Zea mays). Understanding the molecular regulation of flowering and genotypic variation therein is important for molecular breeding and crop improvement. This paper reviews the regulation of flowering in different crop species with a particular focus on how photoperiod-related genes facilitate adaptation to local environments.